Helper Dependent Adenovirus Vectors: Progress and Future Prospects - Cots, Dan; Bosch, Assumpció; Chillón, Miguel (Current Gene Therapy, 2013)
Sixteen years after Graham and coworkers described the most used system for generating helper-dependent adenovirus (HDAd) vectors, production systems have evolved considerably, and most resulting preparations have titres of 1 × 1013 IU/ml (infection units/ml) and very low helper contamination levels (<0.1%). These advances in production, as well as the attractive characteristics of these vectors (large insert capacity and low cell immune response compared with first-generation Ad vectors) make them very interesting for many research purposes as they have become more accessible to the scientific community. In this review we summarise the latest strategies for producing HDAd vectors, describe the main areas of interest for which HDAd vectors are being used, and comment on the future prospects for HDAd vectors in gene therapy.
Keywords: Adenovirus